Evaluasi Kualitas Radiograf Periapikal Teknik Bisektris : Kesalahan Penempatan Sudut Penyinaran dan Film - Suparno, Nilasary Rochmanita; Faizah, Ariyani; Zahra, Haditsa Aulia (Poltekkes Kemenkes Semarang, 2024)
Background: The bisecting angle technique of periapical radiography is more often used in dental practice because the technique is practically adjustable and the patient's ability to adapt is better. Radiograph results are influenced by operator and patient factors, so management that is not optimal can cause a decrease in the quality of the radiograph, which affects interpretation, diagnosis, and treatment planning. The study aimed to determine the quality and frequency of errors in periapical radiographs using the bisecting technique due to errors in X-ray angulation and film placement at the Soelastri Dental and Oral Hospital (RSGM), University of Muhammadiyah Surakarta (UMS).Methods: The type of research is descriptive observational quantitative research with a retrospective approach. A total of 300 bisecting technique periapical radiographs from patients at RSGM Soelastri UMS in January–December 2021 who met the inclusion and exclusion criteria were taken in random stratification and evaluated. Radiographs are compared to ideal quality and given a National Radiological Protection Board (NRPB) rating, as well as looking at the frequency of errors that occur.Results: The rating most often obtained on periapical radiographs using the bisecting technique in the study was 2 for 181 radiographs (60.33%). The frequency of X-ray angulation errors was 62.94%, while the frequency of film placement errors was 37.06%. The highest error in X-ray angulation was cone cutting at 49.13%, while the error in film placement was in the form of apical cuts at 25.65%.Conclusions: The quality of periapical radiographs using the bisecting technique at the Radiology Installation at RSGM Soelastri UMS in the period January to December 2021 generally has a rating of 2 (diagnostically acceptable) according to the NRPB, and errors are still found in the angulation of the X-ray tube and film placement.